2021
DOI: 10.1186/s12913-020-06005-8
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging gains from African Center for Integrated Laboratory Training to combat HIV epidemic in sub-Saharan Africa

Abstract: Background In sub-Saharan Africa, there is dearth of trained laboratorians and strengthened laboratory systems to provide adequate and quality laboratory services for enhanced HIV control. In response to this challenge, in 2007, the African Centre for Integrated Laboratory Training (ACILT) was established in South Africa with a mission to train staffs from countries with high burdens of diseases in skills needed to strengthen sustainable laboratory systems. This study was undertaken to assess t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
0
4
0
1
Order By: Relevance
“…Differentiated service delivery applies across the HIV continuum to all three of the 95-95-95 targets (95% of PLHIV should know their status; 95% who know their status should be on ART; 95% of those on ART should be virologically suppressed). 10 Sustaining services that provide adequate VL testing to monitor ART response in patients 3,11 and clearing backlogs to increase the number of persons tested can maintain HIV control during a COVID-19 pandemic. 3,12 A study in Atlanta, United States, showed increased cancellation of appointments during the onset of COVID-19; however, ART adherence improved during the initial month of COVID-19 response.…”
Section: Introductionmentioning
confidence: 99%
“…Differentiated service delivery applies across the HIV continuum to all three of the 95-95-95 targets (95% of PLHIV should know their status; 95% who know their status should be on ART; 95% of those on ART should be virologically suppressed). 10 Sustaining services that provide adequate VL testing to monitor ART response in patients 3,11 and clearing backlogs to increase the number of persons tested can maintain HIV control during a COVID-19 pandemic. 3,12 A study in Atlanta, United States, showed increased cancellation of appointments during the onset of COVID-19; however, ART adherence improved during the initial month of COVID-19 response.…”
Section: Introductionmentioning
confidence: 99%
“…Each of the 32 countries country selected and paid for their biosafety officers, laboratory managers, bench staff, professional trainers, institutional management, and facility engineers. For a more detailed breakdown of demographic characteristics of participants please refer to a previous publication [8].…”
Section: Course Participantsmentioning
confidence: 99%
“…To address the afore mentioned needs the U.S. Centers for Disease Control and Prevention (CDC), the U.S. President's Emergency Plan for AIDS Relief (PEP-FAR), and the South African National Health Laboratory Service (NHLS) launched African Center for Integrated Laboratory Training (ACILT). From 2007 to 2016, ACILT provided free, hands-on training courses for laboratorians with a goal to prepare a competent laboratory workforce, strengthen laboratory systems, enhance diagnostics capacity in SSA [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hal ini akan mengarah pada perbaikan kegagalan usaha kecil dan meningkatkan pertumbuhan ekonomi negara (Rachapaettayakom et al, 2020). Faktor pendukung utama untuk mewujudkan hal tersebut adalah dengan adanya dukungan tim dan manajemen, dan faktor penghambat utama termasuk sumber daya yang tidak mencukupi dan penolakan staf untuk berubah (Shrivastava et al, 2021).…”
Section: Sumber :Penulis 2023unclassified